PENGELOLAAN KECEMASAN DAN KETIDAKPASTIAN DI KALANGAN PENGUNGSI PBB DI SEMARANG - Andrio, Bimo; Rahardjo, Turnomo; Dwiningtyas Sulistyani, Hapsari (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
The main goal of this study is to describe the anxiety and uncertainty management of refugees in Semarang. The research dive deeper into understanding and describing the communication anxiety and uncertainty faces by asylum seekers in Semarang and their struggle to manage it during their interval time for the asylum opportunities. The result of the study itself shows how the anxiety cause by dangerous is their migration journey and their living condition in Indonesia. With limited chance to form an effective communicate with the responsible immigration and United Nations representatives, the asylum seeker force to cope with current and very underwhelming living condition as well as limited access to public service without any meaningful solution or any communications process. There are also evidence of the how the refugees trying to make sense of the situation and starting to open them self to the local in order to reduce their anxiety. It is also worth to mention, even in the limited chance to make any impactful interaction with the IOM in Indonesia, the refugees found ways to extract information about their asylum status in which lower their feeling of uncertainty during this trying time.